2012
DOI: 10.1182/blood-2011-09-378364
|View full text |Cite
|
Sign up to set email alerts
|

MST1 mutations in autosomal recessive primary immunodeficiency characterized by defective naive T-cell survival

Abstract: The molecular mechanisms that underlie T-cell quiescence are poorly understood. In the present study, we report a primary immunodeficiency phenotype associated with MST1 deficiency and primarily char- IntroductionThe study of human T-cell primary immunodeficiencies has enabled the molecular characterization of many diseases caused by Mendelian inheritance of mutated genes [1][2][3][4] and has revealed the function of key molecules in T-cell biology. SCIDs are characterized by complete lack of T-cell developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
252
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(264 citation statements)
references
References 44 publications
10
252
1
1
Order By: Relevance
“…Autosomal recessive nonsense mutations in STK4 result in a PID characterized by bacterial infections, herpetic viral infections, cutaneous viral infections, EBV-driven lymphoproliferation, and structural heart abnormalities (Abdollahpour et al 2012;Nehme et al 2012). CMC was also reported in a portion of patients (Abdollahpour et al 2012).…”
Section: Serine-threonine Protein Kinase 4 (Stk4/mst1) Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autosomal recessive nonsense mutations in STK4 result in a PID characterized by bacterial infections, herpetic viral infections, cutaneous viral infections, EBV-driven lymphoproliferation, and structural heart abnormalities (Abdollahpour et al 2012;Nehme et al 2012). CMC was also reported in a portion of patients (Abdollahpour et al 2012).…”
Section: Serine-threonine Protein Kinase 4 (Stk4/mst1) Mutationsmentioning
confidence: 99%
“…þ T-cell lymphocytopenia with markedly reduced naïve T cells, decreased central memory T cells, and preserved effector memory T cells (Abdollahpour et al 2012;Nehme et al 2012). These patients also exhibit intermittent neutropenia with normal bone marrow neutrophil maturation.…”
Section: Serine-threonine Protein Kinase 4 (Stk4/mst1) Mutationsmentioning
confidence: 99%
“…27 MST1-deficient T cells showed downregulation of FOXO1 expression and upregulation of FAS expression. 28 Recently, it was reported that patients lacking MST1 displayed primary immunodeficiency like features. 29 MST1 was found to be critical for maintenance of lymphocytes and control of unrestricted Epstein-Barr virus(EBV)-induced lymphoproliferation.…”
Section: Gck-ii Kinases Regulate Lymphocyte Adhesion Migration Prolmentioning
confidence: 99%
“…Mst1/2 proteins may also promote apoptosis by interacting and suppressing Akt activation in cancer cells (22). However, T cells from Mst1-deficient mice and human patients exhibit enhanced apoptosis (23)(24)(25) in addition to the mutant phenotypes of impaired adhesion and migration in mice (25)(26)(27)(28)(29), suggesting that Mst1 may exert different cellular functions in tissue/cell type-specific manners (28 …”
Section: Mst2mentioning
confidence: 99%